Alterations of SARS-CoV-2 Evolutionary Dynamics by Pharmaceutical Factors - Matthew Halma; Wei Zhao (​​​​​​​​Infectious Diseases & Immunity)
Abstract. The outbreak of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) has been influenced by the human response to the virus. These responses have undoubtedly impacted the evolutionary dynamics of the virus in ways distinct from a scenario lacking a widespread response. Two important pharmaceutical interventions, vaccination and the utilization of medications, particularly molnupiravir, known to have mutagenic properties, were the focus of this article. The impact of molnupiravir on human health was evaluated through 3 mechanisms: viral resistance, mutagenesis of SARS-CoV-2, and mutagenesis occurring in patients undergoing treatment with molnupiravir. These mechanisms, as well as the impact of vaccination, have inadvertently given rise to unforeseen challenges in the management of the COVID-19 crisis. Taking a systems view in future pandemic responses, and taking into account the evolution of the pandemic virus, may be critical to ending the pandemic at an earlier date.